CFD simulation and PIV validation of the gas/liquid behavior in an UASB reactor - D’Bastiani,Camila (2020)
ABSTRACT As the world population increases, the need to develop more efficient wastewater treatment systems requires the use of new technologies. Software aided project and optimization of bioreactors and bioprocesses have become a matter of interest in recent years, especially due to the advance in the state-of-the-art of computational resources. This work aimed to perform gas/liquid numerical simulations using the Fluent 16.2 software and to validate this model through Particle Image Velocimetry (PIV) and shadow imaging techniques. Eulerian-Eulerian, laminar, tridimensional and transient simulations were carried out. The results for the mass imbalance for the gas and liquid phases, gas volumetric fraction, gas velocity, bubble size, liquid magnitude and upflow velocity and the velocity profiles for the liquid phase were successfully validated against experimental data. Concerning the dispersed phase, it was found a difference of 4.37% for the gas volumetric fraction between experiments and simulations. Simulated results showed a difference for the bubble mean velocity of 1.73% when compared with shadow imaging results. No coalescence was observed along the experiments, and the flow regime was characterized as dispersed bubble flow. Regarding the liquid phase, it was found a difference of 3.2% for the mean velocity, between simulated and PIV results. Simulated and experimental velocity profiles showed a better agreement at the center of the reactor. Some differences were observed in those profiles, due to geometry simplifications assumed in order to get a better mesh. Considering the good agreement between simulation and experiments, the model was considered validated.